The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.bcp.2009.02.018
|View full text |Cite
|
Sign up to set email alerts
|

The kinase inhibitor O6-cyclohexylmethylguanine (NU2058) potentiates the cytotoxicity of cisplatin by mechanisms that are independent of its effect upon CDK2

Abstract: O(6)-Cyclohexylmethylguanine (NU2058) was developed as an inhibitor of CDK2 and was previously shown to potentiate cisplatin cytotoxicity in vitro. The aim of this study was to investigate the mechanism of cisplatin potentiation by NU2058. SQ20b, head and neck cancer cells were treated for 2h with NU2058 (100 microM) and then for a further 2h with cisplatin and NU2058. NU2058 increased cisplatin cytotoxicity, by clonogenic assay, with a dose modification factor (DMF) of 3.1. NU2058 increased total intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…This compound, VE-821, also blocked phosphorylation of CHK1 at ser345 (Reaper et al , 2011). We have taken a different approach, based on the observation that NU2058 and NU6027 sensitised cells to cisplatin independently of their CDK2 inhibitory activity (Harrison, 2009; Harrison et al , 2009). We developed a cell-based assay using ATR kinase-dead cells, and used it to demonstrate that NU6027 is, in fact, a more potent inhibitor of ATR than CDK2 in living cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound, VE-821, also blocked phosphorylation of CHK1 at ser345 (Reaper et al , 2011). We have taken a different approach, based on the observation that NU2058 and NU6027 sensitised cells to cisplatin independently of their CDK2 inhibitory activity (Harrison, 2009; Harrison et al , 2009). We developed a cell-based assay using ATR kinase-dead cells, and used it to demonstrate that NU6027 is, in fact, a more potent inhibitor of ATR than CDK2 in living cells.…”
Section: Discussionmentioning
confidence: 99%
“…The CDK2 inhibitor, NU2058, (Arris et al , 2000), profoundly sensitises cells to cisplatin cytotoxicity independently of CDK2 inhibition (Harrison et al , 2009) and the analogous pyrimidine, NU6027 (2,6-diamino-4-cyclohexyl-methyloxy-5-nitroso-pyrimidine; Supplementary Figure 1) has similar effects (Harrison, 2009). These observations, coupled with the known cisplatin sensitisation by ATR knockdown led us to investigate whether NU6027 inhibited ATR.…”
mentioning
confidence: 99%
“…NU6027 (2,6-diamino-4-cyclohexyl-methyloxy-5-nitroso-pyrimidine) was identified as a CDK2 inhibitor 78 . Peasland et al found out that NU6027 was a more potent inhibitor of ATR (IC 50 :2.8-2.9 Ī¼M) than of CDK2 (IC 50 : 10 Ī¼M).…”
Section: Atr Inhibitorsmentioning
confidence: 99%
“…[ 6 ] Interestingly, NU2058 was also reported to exert a CDK2ā€independent effect on cancer chemoresistance. [ 7 ] To date, the anticancer bioactivity of NU2058 in CRC and the underlying mechanism have not been reported.…”
Section: Introductionmentioning
confidence: 99%